Roles of the Employees in Creating an Efficient Team (Research Bulletins of the Faculty of Economic Sciences, 2015)
Team's work efficiency depends on inner and outer factors. The importance lies in leadership, individual features, expectations of the employees as well as in the development process of both single members and the entire team. Moreover, what matters at the team's work efficiency is not only education and working skills but also character type of each employee. Roles in team are created in accordance with individual characteristics of the employees and are important in terms of the team functioning as a whole.
Keywords: staff; organization; roles; work; efficiency